The Implementation of Sharia banking in Indonesia Pertaining Sustainable Sharia Measurement - Ahmad Afif; Muh. Nadratuzzaman Hosen (Al Qalam, 2022)
Abstract: The purpose of this paper is to investigated how effective the GCG/annual report, and Sustainability, are in presenting information on the performance of Sharia banking in Indonesia applying sharia reporting criteria. This analysis will bring up the report based on a copy of the Financial Services Authority of the Republic of Indonesia's Circular Letter No. 10 / SEOJK.03/2020 on Transparency and Report Publication for Islamic Commercial Banks and Sharia Business Units. In the GCG and sustainable report, the variables of banking size, ratio, and Sharia Supervisory Board size. Secondary data from 12 Islamic banks from 2019 and 2020 is being used in study, that either takes a descriptive quantitative approach. Furthermore, the determined indicators will be sorted using factor analysis with SPSS 12. The GCG/annual report shows better performance than the sustainability report, as evidenced by significant values in the whole test and factor analysis stages. 11 Islamic commercial banks, on the other contrary, do not have a test stage but do have a detailed study. Meanwhile, the sustainability report is not greater to the GCG/annual report because, while the sustainability report is on average significant, it lack variable testing stages that are comparable with the positive influence on the produced factors. The OJK would update POJK 51 / POJK.03/2017 well about Implementation of Sustainable Finance for Financial Services Institutions, Issuers, and Public Companies for sharia report indicator points, along with other observations and recommendations. Second, Islamic banks must comply to protracted sharia reporting standards. Keywords: Sharia Report, GCG/Annual Report, and Sustainability Report.